2019
DOI: 10.1002/esp.4558
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bedform dynamics and bedload sediment flux in sandy braided rivers from airborne and satellite imagery

Abstract: Images from specially‐commissioned aeroplane sorties (manned aerial vehicle, MAV), repeat unmanned aerial vehicle (UAV) surveys, and Planet CubeSat satellites are used to quantify dune and bar dynamics in the sandy braided South Saskatchewan River, Canada. Structure‐from‐Motion (SfM) techniques and application of a depth‐brightness model are used to produce a series of Digital Surface Models (DSMs) at low and near‐bankfull flows. A number of technical and image processing challenges are described that arise fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 75 publications
0
19
0
2
Order By: Relevance
“…This technique, known as GNSS-supported aerial triangulation (GNSS-AT; Benassi et al, 2017), has been shown to result in sub-GSD horizontal accuracy without the use of GCPs (Mian et al, 2015;Fazeli et al, 2016;Hugenholtz et al, 2016;Benassi et al, 2017;van der Sluijs et al, 2018). Published applications of this technique in the geosciences are so far limited (van der Sluijs et al, 2018;Strick et al, 2018), and no studies have yet examined the appropriateness of this technique for the study of glacial dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, known as GNSS-supported aerial triangulation (GNSS-AT; Benassi et al, 2017), has been shown to result in sub-GSD horizontal accuracy without the use of GCPs (Mian et al, 2015;Fazeli et al, 2016;Hugenholtz et al, 2016;Benassi et al, 2017;van der Sluijs et al, 2018). Published applications of this technique in the geosciences are so far limited (van der Sluijs et al, 2018;Strick et al, 2018), and no studies have yet examined the appropriateness of this technique for the study of glacial dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their previous identification at the Stoer Peninsula (e.g., Ghinassi and Ielpi, 2018), such packages were recognized across the Torridonian outcrop belt over the course of this study (n = 85). However, such packages are not conclusively diagnostic of meandering planforms because lateral accretion can occur on the flanks of mid-channel braid bars during waning flood (e.g., Best et al, 2003;Strick et al, 2018). Conversely, as all rivers have a degree of variability in planview morphology (e.g., Ethridge, 2011), it is possible that some of the lateral-accretion deposits recognized in this study record deposition in locally sinuous channels.…”
Section: Fluvial Stylementioning
confidence: 79%
“…The Castlegate Sandstone comprises amalgamated fluvial channel-belt deposits which, architecturally, are dominated by barforms (e.g., mid-channel bars) (Miall, 1993(Miall, , 1994). Therefore, cross-sets that we measured in the Castlegate Sandstone likely preserve bedforms that were influenced by barform migration, and it is possible that low CV(hxs) values observed in these cross-sets reflect bedform disequilibrium dynamics associated with the hierarchy hypothesis, especially given that unit bar migration typical of braided rivers can be comparable to dune migration rates (Strick et al, 2019). Conversely, fluvial strata of the Blackhawk Formation and Ferron Sandstone comprise major channelized sandstone bodies Chidsey et al, 2004;Hampson et al, 2013;Flood & Hampson, 2014) which, while abundant in barforms (e.g., laterally accreted point bar deposits; Fig.…”
Section: Implications Of the Hierarchy Hypothesis For Bedform Preservationmentioning
confidence: 98%